Legal power of land tenure statement as proof of land ownership disputes from the perspective of indonesian basic agrarian law - Merry Christiangie; Harsanto Nursadi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Ownership of land rights is a very important thing to be considered by the Indonesian people. In Indonesia, proof of ownership of recognized land rights is only a certificate, as stipulated in the UUPA and Government Regulation Number 24 of 1997 concerning Land Registration. In the national land law, the Land Certificate has been regulated as a letter that contains physical evidence of the ownership of a plot of land used for the land registration process. The problems raised in this study are how the function of the Land Certificate and the power of proving the Land Certificate in land cases. The Land Certificate only functions as an accompanying document in land registration. However, in the latest provisions regulated in PP 18/2021, it is stated that the Land Certificate only serves as an indication in the context of land registration. The strength of the Land Certificate is not strong, because the UUPA and PP 24/1997 have stated that the evidence of legal ownership of land rights is the Land Rights Certificate. The Land Certificate is not a strong piece of evidence, because it is proof of ownership made under the hand.